Microbial Transformation of 2,4,6-Trinitrotoluene in Aerobic Soil Columns - Bruns-Nagel, D. (1996)
2,4,6-Trinitrotoluene (TNT)-contaminated soil material of a former TNT production plant was percolated aerobically in soil columns. Nineteen days of percolation with a potassium phosphate buffer supplemented with glucose or glucose plus ammonium sulfate caused an over 90% decline in the amount of extractable nitroaromatics in soils containing 70 to 2,100 mg of TNT per kg (dry weight). In the percolation solution, a complete elimination of TNT was achieved. Mutagenicity and soil toxicity were significantly reduced by the percolation process. 4-N-Acetylamino-2-amino-6-nitrotoluene was generated in soil and percolation fluid as a labile TNT metabolite.